Voluntary disclosure incentives: Evidence from the municipal bond market - Cuny, Christine (Journal of Accounting and Economics, 2016)
I investigate the trade-off between capital market incentives, reputational concerns, and administrative costs in the public disclosure decisions of municipal bond issuers. After Ambac׳s bankruptcy, issuers of insured debt increase disclosure relative to issuers of uninsured debt. After local per capita income declines or expenditures increase, issuers, particularly those with strong electoral incentives and weak voter oversight, reduce disclosure. After the implementation of an online filing repository, issuers with few dissemination channels increase disclosure relative to other issuers. Overall, my findings support a positive relationship between voluntary disclosure, risk, and low-cost dissemination, to the extent reputational capital is not threatened.